2005
DOI: 10.1074/jbc.m502276200
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Translation of the Respiratory Syncytial Virus M2 Open Reading Frames Requires Upstream Sequences

Abstract: We have investigated the mechanism of the translation of the second open reading frame (ORF) of the respiratory syncytial virus M2 transcript that uses a novel coupled translation process requiring prior translation of the upstream ORF. The second M2-2 ORF sequences play no role in the coupling process and can be replaced with other gene sequences. Surprisingly, the overlap region of the two ORFs alone was not sufficient for coupled translation to occur. An analysis of the sequences required for the coupling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 25 publications
(26 reference statements)
3
46
0
Order By: Relevance
“…Similar results were also obtained for RHDV, where an upstream element of nearly identical length and location was necessary for translation of the 3Ј-terminal ORF (25). Influence of upstream sequences on a termination/reinitiation process was also found for the respiratory syncytial virus (RSV) M2 RNA with the two overlapping ORFs M2-1 and M2-2 (24). In RSV, the essential upstream sequence element is somewhat larger and the decrease in translation efficiency of the downstream ORF in consequence of proceeding deletions in M2-1 occurs over a longer distance, so that it is not clear at the moment whether the initiation of translation of M2-2 is mechanistically equivalent to the process described here for caliciviruses.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar results were also obtained for RHDV, where an upstream element of nearly identical length and location was necessary for translation of the 3Ј-terminal ORF (25). Influence of upstream sequences on a termination/reinitiation process was also found for the respiratory syncytial virus (RSV) M2 RNA with the two overlapping ORFs M2-1 and M2-2 (24). In RSV, the essential upstream sequence element is somewhat larger and the decrease in translation efficiency of the downstream ORF in consequence of proceeding deletions in M2-1 occurs over a longer distance, so that it is not clear at the moment whether the initiation of translation of M2-2 is mechanistically equivalent to the process described here for caliciviruses.…”
Section: Discussionsupporting
confidence: 69%
“…The biochemistry behind such a termination/reinitiation process is not fully understood. In two cases, the implication of upstream sequences has been reported although the function of these sequences is not known (24,25).…”
mentioning
confidence: 99%
“…The first ORF from each gene was amplified by PCR and the CAT reporter gene was inserted to replace the coding region of the second ORF in each gene immediately downstream from the overlap between ORF-1 and ORF-2. The entire construct was inserted into pBlueScribe as previously described (Ahmadian et al 2000;Gould and Easton 2005). This general structure of the constructs is illustrated in Figure 1A including the stop mutant.…”
Section: Methodsmentioning
confidence: 99%
“…These data also demonstrated that translation of the second ORF is not due to the presence of an IRES sequence. The region of overlap of the M2 ORF-1 and ORF-2 alone is not sufficient to achieve coupled expression but also requires additional sequences located within the M2-1 ORF (Gould and Easton 2005). Importantly, in all of these studies the data were generated in cells in which no other virus genes were being expressed, indicating that the coupled translation process is, in principle, an option available to all cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation